Obesity Does Not Increase Perioperative Outcomes in Older Patients Undergoing Thoracoscopic Anatomic Lung Cancer Surgery - Tong, Chaoyang; Li, Tingting; Shen, Yaofeng; Zhu, Hongwei; Zheng, Jijian; Wu, Jingxiang (Frontiers in Oncology, 2022)
Objectives: To investigate the relationship between obesity status and perioperative outcomes in elderly patients undergoing thoracoscopic anatomic lung cancer surgery. Methods: From January 2016 to December 2018, we performed a monocentric retrospective cohort study among 4164 consecutive patients aged 65 years or older who underwent thoracoscopic anatomic lung cancer surgery at Shanghai Chest Hospital. Two groups were stratified by body mass index (BMI): nonobese (BMI<28kg/m2) and obese status (BMI≥28kg/m2). Using a 1:1 propensity score matching (PSM) analysis to compare perioperative outcomes between two groups. Results: 4035 older patients were eventually enrolled, with a mean age of 69.8 years (range: 65-87), and 305 patients were eligible for obese status, with a mean BMI of 29.8±1.7kg/m2. Compared with nonobese patients, obese patients were more likely to have higher rates of intraoperative hypoxemia (1.2% vs 3.9%, P=0.001) and new-onset arrhythmia (2.3% vs 4.3%, P=0.034). The difference in intraoperative transfusion and conversion rates and postoperative outcomes regarding pulmonary complications, new-onset arrhythmia, transfusion, length of hospital stay, 30-day readmission and hospitalization costs between two groups were not significant (P>0.05). After a 1:1 PSM analysis, the difference in both intraoperative and postoperative complications among two groups were not significant (P>0.05). In subgroup analysis, patients with BMI≥30kg/m2 had a similar incidence of perioperative complications compared to patients with BMI between 28 and 30 kg/m2 (P>0.05). Conclusions: Our research data support evidence for "obesity paradox" and also contribute the growing body of evidence that obesity in older patients should not exclude candidates for thoracoscopic anatomic lung cancer surgery.